Role of farmers’ entrepreneurial orientation, women’s participation, and information and communication technology use in responsible farm production: a step towards sustainable food production - Shahbaz, Pomi; Haq, Shamsheerul; Abbas, Azhar; Azadi, Hossein; Boz, Ismet; Yu, Mark; Watson, Susan (Frontiers in Sustainable Food Systems, 2023)
Responsible production is essential for sustainable development and for ensuring global food security. The concept of responsible production has been well studied in other sectors of the economy, but has yet to gain recognition in the agricultural sector. Therefore, this study examined responsible production in the context of agriculture and the factors affecting responsible farm production in the developing country of Pakistan. Face-to-face interviews were conducted to collect data from 196 farmers selected using the multistage random sampling method. An independent sample t-test, chi-square test, and ordered probit model were used to analyze the data. The responsible farm production index was estimated based on the climate change adaptation, resource efficiency, carbon footprints, and economic returns of each farm. The mean value of the responsible farm production index is 0.69. The farmers were divided into low-, moderate-, and highly responsible farm producers using cluster analysis. More than 36% of farms were highly responsible. The results revealed that women’s participation in farming activities, extension services, the use of information and communication technologies, and farmer entrepreneurial orientation dimensions significantly affected responsible farm production. Farm producers using the Internet for agriculture had a 1.4% points higher probability of belonging to the highly responsible farm producer category compared to those who did not use the Internet to obtain agricultural information. Farms with women’s participation in agricultural activities were 33.5% points more likely to belong to the highly responsible farm producer category than farms where only males perform agricultural operations. Therefore, women’s empowerment and farmers’ entrepreneurial skills are absolute necessities of responsible farming. This study piques the interests of stakeholders while also adding to the scant body of knowledge on responsible farm production around the world. Furthermore, this study is critical for developing a roadmap for long-term sustainable agricultural development.